Análise físico-química, compostos fenólicos, capacidade antioxidante, carotenoides totais e vitamina c da polpa, casca e semente da fruta gabiroba - Pasquotto, Ieda (Universidade Federal de São Carlos, 2020)
Gabiroba (Campomanesia xanthocarpa) is a fruit of the Myrtaceae family, native to the Atlantic Forest and Brazilian cerrado. It is widely used in folk medicine and consumed fresh in the form of liquors and juices. This work aimed to evaluate the physicochemical composition and some biochemical properties of gabiroba proven in the interior of the state of São Paulo. The fruits were harvested in the city of Campina do Monte Alegre (SP) manually and randomly. Physicochemical analyzes, proximate composition of the different parts of the fruits (peel, pulp and seed) were carried out and the extracts obtained by shaking and ultrasound were analyzed in relation to their content of total phenolic compounds, total carotenoids, vitamin C and antioxidant capacity. Their physical and chemical characteristics of the fractions were evaluated for the parameters longitudinal and transverse diameter (mm), mass (g) and pulp yield (%). For the preparation of the samples, the fruits were selected, sanitized, separated, crushed and frozen and they were evaluated for the levels of chemical composition and bioactive compounds. Regarding the proximate composition, the fractions showed high levels of moisture and fibers and the results showed high levels of phenolic compounds and vitamin C in addition to high antioxidant capacity, demonstrating the great potential of the fruit to be marketed and consumed in different ways.
Physical chemical analisys, phenolic compounds, antioxidant activity, carotenoids and vitamin C of pulp, peel and seed of gabiroba (Campomanesia xanthocarpa) fruit
Keywords: Compostos bioativos; Frutas exóticas; Extração; Bioactive compounds; Exotic fruits; Extration; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES